Socio-epidemiological characterization of human leptospirosis in the Federal District, Brazil, 2011-2015 - Santos, Ivanildo de Oliveira Correia (2018)
INTRODUCTION: Human leptospirosis (HL) in the Federal District (DF), Brazil, is endemic and requires studies to characterize the socio-epidemiological profile of the vulnerable population. METHODS: Seventy-nine autochthonous cases of HL between 2011-2015 were analyzed based on the databases of the Epidemiological and Environmental Health Surveillance Department, DF. RESULTS: The male population aged 31-45 years represented 86% of the leptospirosis cases; most belonged to the social classes D and E. CONCLUSIONS: In the DF, preventive measures should be concentrated on economically active male adults of social classes C, D, and E with the aim of promoting health.